2002
DOI: 10.1097/00002060-200205000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Physical Fitness of Lower Limb Amputees

Abstract: This study showed that the physical fitness of amputees was clearly lower than that of the able-bodied subjects and that the amputees were able to recover from a poorly conditioned status after endurance training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
3
7

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 10 publications
4
51
3
7
Order By: Relevance
“…Hence, the TFA participants have considerably lower cardio-respiratory fitness than able-bodied subjects with similar age, height, weight, sex and selfreported fitness. In this regard, it is argued that only those amputees who have adequate fitness will become successful prosthetic users 4 . Consequently, TFA should engage in regular physical activity to reduce the risk of further reductions of their cardio-respiratory fitness and to ensure effective prosthetic ambulation.…”
Section: Validity Of the Walking Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the TFA participants have considerably lower cardio-respiratory fitness than able-bodied subjects with similar age, height, weight, sex and selfreported fitness. In this regard, it is argued that only those amputees who have adequate fitness will become successful prosthetic users 4 . Consequently, TFA should engage in regular physical activity to reduce the risk of further reductions of their cardio-respiratory fitness and to ensure effective prosthetic ambulation.…”
Section: Validity Of the Walking Protocolmentioning
confidence: 99%
“…e.g. 2,3,4,5 Using mainly test protocols based on one-leg cycle ergometry or upper body ergometry, these studies collectively report very low VO2max values compared to predicted values for healthy individuals of the same age and sex. 6 A low level of VO2max for transfemoral amputees (TFA) may be caused by several factors: The VO2max may be systematically underestimated due to the choice of test protocol, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning aerobic capacity, Chin et al 13 found that the physical fitness of young, traumatic amputees was lower than that of able-bodied subjects. The maximum oxygen uptake (VO 2 max) of the amputee group was 18.8 mL/kg per min (SD 4.9) whereas the VO 2 max of the able-bodied group was 23.5 mL/kg per min (SD 3.2), a statistically significant difference.…”
Section: Status and Development Of Physical Capacitymentioning
confidence: 99%
“…Such a strong difference should be observable in our experiments, even at low workloads, if co-contraction, contracture and spasticity are responsible for the increase in energy expenditure. A similar protocol was used by Chin et al [21] to evaluate the fitness of young adult traumatic amputees (mean age: 26.0 AE 5.7 years) pedalling one lower limb at a time with their healthy lower limb. The mean maximal workload that patients could reach was 67.6 AE 20.2 W, whereas healthy subjects could reach 102.4 AE 33.6 W. This low working capacity could also be explained by cardiovascular deconditioning and comorbidities [22], neurological impairments [24], muscular atrophy, decreased lean tissue mass and increased intramuscular-fat in paretic lower limb [23].…”
Section: Working Capacitymentioning
confidence: 99%